Rancang Bangun Aplikasi Informasi Kegiatan Keagamaan Pada Masjid Agung Islamic Center Rokan Hulu Berbasis Android - Fitra Yamita; Salhazan Nasution (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Great Mosque Islamic Center Rokan Hulu is the best national mosque in Indonesia and also as an icon of Rokan Hulu Regency which has the nickname of the Country of Thousand Suluk. This mosque is also a religious tourist place. Therefore, this mosque has many religious activity agendas that are in the spotlight of the wider community. The lack of information dissemination on religious activities is a major problem that must be overcome. Communities often get non-updated information and outdated information. Mobile Application of Religious Activities for the Great Mosque Islamic Center Rokan Hulu with Push Notification is the solution to these problems. This application uses the push notification method so that users easily get information on religious activities through automatic notifications on the user's smartphone and also as a reminder of the schedule of religious activities. Users can also set up information on religious activity information they want to get through the notification configuration menu. Besides, this application also has a menu about mosques that contain information on the Great Mosque Islamic Center Rokan Hulu such as prayer schedules, locations, descriptions, and galleries.Keywords: The Great Mosque Islamic Center Rokan Hulu, Android Application, Push Notification, Activities Information.